2022
DOI: 10.3389/fcell.2021.723466
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Elucidation of the Aneuploidy Landscape and Identification of Aneuploidy Driver Genes in Prostate Cancer

Abstract: Aneuploidy is widely identified as a remarkable feature of malignancy genomes. Increasing evidences suggested aneuploidy was involved in the progression and metastasis of prostate cancer (PCa). Nevertheless, no comprehensive analysis was conducted in PCa about the effects of aneuploidy on different omics and, especially, about the driver genes of aneuploidy. Here, we validated the association of aneuploidy with the progression and prognosis of PCa and performed a systematic analysis in mutation profile, methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 107 publications
(122 reference statements)
1
2
0
Order By: Relevance
“…Through Kaplan-Meier plotter analysis, significant differences were observed in the survival curves between patients with high and low expression of FAXDC2. This analysis confirmed that FAXDC2 expression is downregulated in prostate cancer and neuroblastoma and low expression of FAXDC2 is indicative of an unfavorable prognosis for these diseases (24,25), in accordance with the experimental findings of the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Through Kaplan-Meier plotter analysis, significant differences were observed in the survival curves between patients with high and low expression of FAXDC2. This analysis confirmed that FAXDC2 expression is downregulated in prostate cancer and neuroblastoma and low expression of FAXDC2 is indicative of an unfavorable prognosis for these diseases (24,25), in accordance with the experimental findings of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Controlling the content of cholesterol and sphingomyelin can artificially achieve the dynamic remodeling of lipid rafts ( 22 , 23 ), thereby changing the transduction properties of intracellular signals. It has been reported that the expression of FAXDC2 is downregulated in prostate cancer and neuroblastoma and low expression of FAXDC2 is an unfavorable factor for disease prognosis ( 24 , 25 ). Another study has shown that FAXDC2 can regulate macrophage differentiation by regulating ERK signaling-related mechanisms ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated miRNAs as a direct or indirect consequence of impaired tRNA processing correlated with reduced mRNAs involved in mitochondrial function and potentiation of inflammation and cell growth in the KO and A537T mutant mice compared with controls (Appendix Fig S10 A), such as miR‐10a‐5p that correlated with reduced the expression of the mitochondrial thiosulfate sulphur transferase ( Tst ; Fig 6E and F ). Reduced miRNAs such as miR‐122‐5p and miR‐383‐5p/miR‐338‐3p correlated with an increase of mRNAs involved in cell transformation ( Gldc ; Liu et al , 2021 ), inhibition of apoptosis ( Bcl2 ), prostate tumorigenesis ( Trp63 ; Pignon et al , 2013 ) and hypoxia ( Hif3a ; Peng et al , 2022 ) in the KO and A537T mutant mice compared with controls (Fig 6E and F ).…”
Section: Resultsmentioning
confidence: 88%